BRUXISM PADA ANAK-ANAK DAN PERAWATANNYA - Shita, Amandia Dewi Permana (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2010)
Bruxism is the medical term for the grinding of teeth or the clenching of jaws. Bruxism often occurs during deep sleep or while under stress. No one knows why bruxism happens. But in some cases, kids may grind because the top and bottom teeth are not aligned properly. Others do it as a response to pain, such as an earache. Kids might grind their teeth as a way to ease the pain, just as they might rub a sore muscle. Stress,usually nervous tension or anger is another cause. For instance, a child might worry about a test at school or a change in routine. Some kids who are hyperactive also experience bruxism. And sometimes kids with other medical conditions (such as cerebral palsy) or on certain medications can develop bruxism. The most common solution is usually a recommendation from the mouth guard. Wear a mouth guard at night will prevent the child from grinding their teeth and night, and has a very high success rate in reducing the habit.